The information behavior of Philippine choristers: the basic for creating a collection development policy for the Philippine Madrigal Singers Library - Tacuboy, Ma. Nicole R.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2021)
Choral music training and workshops have become accessible through the outreach programs of the Philippine Madrigal Singers (Madz), but Philippine choristers still experience difficulty in meeting their information needs, Selected members of the MADZ serve as the sample of the Philippine choral community. Dervin’s Sense-Making Theory (1999) served as a guidance of the online interviews. The information needs of choristers are listed. The frequent themes are analyzed using Godbold’s Model of Information Behavior (2006) to interpret the gap navigation occurring in each example. Choral scores are the top information need for Philippine choristers and they value connecting with other choristers in order to meet their information needs. Developing a Philippine Choral Music Catalog is recommended to guide choristers into rightful access when meeting their information needs. Further study recommendations: demography of Philippine choristers and analyzing the accessibility of their information needs, the need for local sheet music publishers and, research in cataloging standards for choral music, and researching the need for digital reference services in the Philippine choral community.
Thesis
Keywords: Information behavior; Collection development (Libraries).; Philippine Madrigal Singers Library